Sob o domínio da cruz: a construção de um território e patrimônio cultural em Sergipe - Bonjardim, Solimar Guindo Messias (2014)
The Catholic Church is the greatest institution of religious, cultural, political and economic nature of visible structure that still exists in operation. It is recognized for the high hierarchy, the bureaucracy and the organization of its territory delimited from practices developed for its expansion and maintenance. In this universe, we ask about the current space occupied by the Catholic Church and the actions developed by it to consolidate its dominant position in Sergipe. We also try to understand the logic of this process by interpreting the existing relations of power for its operation. Thus, we make the thesis that the Catholic Church maintains its territory, landscape and heritage through power relations of symbolic ando of representation. So, this study aimed to identify: the factors that have contributed and, in a certain way, influenced the actions of the Catholic Church in the creation of its territories; territorial logics adopted; strategies of the institution to act on identity and approach of the devotee. To make the interpretation of the Catholic Church, we use the cultural and religious approach of geography combined with methodological purpose of qualitative and quantitative analysis, linked to three procedures for understanding the reality: a simple observation for description, the data collection in primary and secondary sources for the quantification and qualification and interviews for the representation. As a result, we understand that the Catholic Church is an established institution that has passed by a territorial reframing and that administers and consolidates its territory and landscape through private actions which form in Sergipe, two trends of the Catholic Church in the same territory: the South institution, which comprises two dioceses, more traditional followers of the precepts established by the bishops of Brazil; and Northern dioceses, which by reason of popular Catholicism, has a profile of closest approach of the Catholic Church and its ideals with the devotees.